Maternal serum leptin concentration in gestational diabetes - Sedigheh Soheilykhah; Mahdieh Mojibian; Soodabeh Rahimi-Saghand; Maryam Rashidi; Hossein Hadinedoushan (Elsevier, 2011)
Objective: The aim of this study was to evaluate fasting serum leptin concentration and its relation to insulin resistance in women with gestational diabetes mellitus (GDM) and gestational impaired glucose tolerance (IGT). Materials and Methods: This case-control study, at 28 weeks of gestation, measured serum concentration of fasting leptin, insulin, and homeostatic model assessment index in three groups, GDM, IGT, and normal control, and compared them with each other. Results: The serum leptin level was significantly higher in women with GDM than in the two other groups (p=0.03). In women with GDM and IGT, leptin was significantly positively related with insulin and homeostatic model assessment index (r=0.221, p=0.03) and (r=0.246, p=0.03), respectively. In all of the participants, there was a significant correlation between leptin and body mass index before pregnancy (r=0.416, p=0.001). Conclusion: Our data showed that serum leptin level was higher in GDM and had a positive correlation with insulin resistance. Our findings suggest that high leptin levels might be a risk factor for GDM and IGT in pregnant women.